Hysteresis in Import Prices: The Beachhead Effect - Baldwin, Richard (American Economic Review, 1988)
[This paper shows that temporary exchange rate fluctuations can have persistent (i.e., hysteretic) effects on trade prices and quantities. Specifically, if market-entry costs are sunk, sufficiently large real exchange rate shocks can alter domestic market structure and thereby induce hysteresis. This simple idea idea has strong implications for exchange rate theory, trade policy, and the estimation of trade equations. Empirical evidence suggests that the recent dollar overaluation induced hysteris in U.S. import prices.]